Linking Primary and Secondary Care after Psychiatric Hospitalization: Comparison between Transitional Case Management Setting and Routine Care for Common Mental Disorders - Bonsack, Charles; Golay, Philippe; Gibellini Manetti, Silvia; Gebel, Sophia; Ferrari, Pascale; Besse, Christine; Favrod, Jérome; Morandi, Stéphane (Frontiers in Psychiatry, 2016)
Objectives To improve engagement with care and prevent psychiatric readmission, a transitional case management intervention has been established to link with primary and secondary care. The intervention begins during hospitalization and ends 1 month after discharge. The goal of this study was to assess the effectiveness of this short intervention in terms of the level of engagement with outpatient care and the rate of readmissions during 1 year after discharge. Methods Individuals hospitalized with common mental disorders were randomly assigned to be discharged to routine follow-up by private psychiatrists or general practitioners with (n = 51) or without (n = 51) the addition of a transitional case management intervention. Main outcome measures were number of contacts with outpatient care and rate of readmission during 12 months after discharge. Results Transitional case management patients reported more contacts with care service in the period between 1 and 3 months after discharge (p = 0.004). Later after discharge (3–12 months), no significant differences of number of contacts remained. The transitional case management intervention had no statistically significant beneficial impact on the rate of readmission (hazard ratio = 0.585, p = 0.114). Conclusion The focus on follow-up after discharge during hospitalization leads to an increased short-term rate of engagement with ambulatory care despite no differences between the two groups after 3 months of follow-up. This short transitional intervention did, however, not significantly reduce the rate of readmissions during the first year following discharge. Trial registration number:ClinicalTrials.gov Identifier NCT02258737.